Knowledge shared and knowledge continually developed: The sharing and growth of a relational and network web across professional, geographical, and national borders. A telling by one of them - Flåm, Anna Margrete (International Journal of Collaborative-Dialogic Practices, 2021)
This paper outlines the growth of a relational and network web across professional,geographical, and national borders. Initiated in the European Arctic North out of a search fornew answers in mental health practices, the network grew across borders of divergences,welcoming all who wanted to learn by talking to and listening to each other in search of newpractices and new answers in ongoing work. It generated a growth of an international networkof knowledge shared and knowledge continually developed. The paper outlines thedevelopment, emerging practices, and the theoretical understandings, including reflectingteams, reflecting processes, and dialogically anchored practices in mental health services andother human areas. Written in the context of an appeal from colleagues in Argentina andParaguay, the paper outlines the story of the network as told by one of the initiators andlongtime partaker from the European Arctic North.